Molecular phylogenetics and phylogeography of sand lizards, Pedioplanis (Sauria: Lacertidae) in southern Africa - Makokha, Jane Sakwa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.